2015
DOI: 10.5598/imafungus.2015.06.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora boodjera sp. nov., a damping-off pathogen in production nurseries and from urban and natural landscapes, with an update on the status of P. alticola

Abstract: A new homothallic Phytophthora species, isolated in Western Australia (WA), is described as Phytophthora boodjera sp. nov. It produces persistent, papillate sporangia, oogonia with thick-walled oospores, and paragynous antheridia. Although morphologically similar to P. arenaria, phylogenetic analyses of the ITS, cox1, HSP90, β-tubulin and enolase gene regions revealed P. boodjera as a new species. In addition, P. boodjera has a higher optimal temperature for growth and a faster growth rate. Phytophthora boodje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 41 publications
4
26
0
1
Order By: Relevance
“…A similar life-style was also suggested for the potentially native P. arenaria and P. constricta in Western Australia (Rea et al 2011). In addition, the four new species may act as damping-off pathogens affecting seedling recruitment, as reported previously for other Phytophthora species (Cohen & Coffey 1986, Simamora et al 2015). This is particularly plausible for P. tyrrhenica considering the high susceptibility of germinating Q. ilex acorns to Phytophthora , due to the poor suberisation and lignification of tissues and restricted allocation of defence compounds (Herms & Mattson, 1992, Martín-García et al 2015, B. Scanu & G. Hardy, unpubl.).…”
Section: Discussionsupporting
confidence: 68%
“…A similar life-style was also suggested for the potentially native P. arenaria and P. constricta in Western Australia (Rea et al 2011). In addition, the four new species may act as damping-off pathogens affecting seedling recruitment, as reported previously for other Phytophthora species (Cohen & Coffey 1986, Simamora et al 2015). This is particularly plausible for P. tyrrhenica considering the high susceptibility of germinating Q. ilex acorns to Phytophthora , due to the poor suberisation and lignification of tissues and restricted allocation of defence compounds (Herms & Mattson, 1992, Martín-García et al 2015, B. Scanu & G. Hardy, unpubl.).…”
Section: Discussionsupporting
confidence: 68%
“…A subsequent molecular re-evaluation of these isolates identified numerous new Phytophthora species ). In combination with subsequent sampling of waterways within native ecosystems (Hüberli et al 2013), 27 taxa have now been identified, including seven known species, 14 species described as a result of these studies (Scott et al 2009;Rea et al 2010Rea et al , 2011Crous et al 2011Crous et al , 2012Crous et al , 2014Jung et al2011;Aghighi et al 2012;Simamora et al 2015;Safaiefarahani et al 2015) and six taxa awaiting description. Most of these newly described species were known only from WA, with only P. multivora known to have a global distribution.…”
Section: Discussionmentioning
confidence: 99%
“…We selected five strains of Phytophthora representing different native species isolated from kwongan vegetation (Simamora et al 2013(Simamora et al , 2015: Phytophthora arenaria (CBS 127950) and four less common species isolated from kwongan vegetation during routine surveys, P. taxon cooljarloo (CLJO100), P. taxon kwongan (TCH009), P. aff. rosacearum (HSA2350) and Phytophthora rosacearum (HSA1658).…”
Section: P H Y T O P H T H O R a I N O C U L U M P R E P A R A T I O Nmentioning
confidence: 99%